Demystifying Science: A Brief History of the Word "Scientist" and the Development of Science as a Profession - Hussain, Md. Jawaid (Voices of Teachers and Teacher Educators, 2023)
The National Education Policy 2020 puts emphasis on ensuring the unity and integrity of all types of knowledge through a ’multi-disciplinary education’ (which transcends traditional subject boundaries and includes science, social science, arts, and humanities). In this paper, an attempt has been made to trace the history of the origin and evolution of the word "scientist’ and provide an overview of the journey from the genesis of the term to its widespread acceptance. In addition, this paper outlines the history of the metamorphosis of science into a profession and discusses the important implications for an inclusive and authentic science education. It is anticipated that the history of the word ’scientist’ and the underlying issues raised in this paper will serve as an interdisciplinary introduction for those with an interest in science education, science and society, and science and human values. This article will also be useful as supplementary reading for science teacher education courses focusing on philosophical and sociological issues.